The expression of follicle-stimulating hormone receptor in ovary and testis (Faculty of Medicine Universitas Indonesia, 2003)
Follicle-stimulating hormone receptor (FSHR) is exclusively expressed in granulose cells of the ovary and Sertoli cells of the testis.The highly cell-specific of gene expression revealed that transcriptional events unique to these two cell types areresponsible for activation of the FSHR gene. Even though its mechanisms are still unclear, several progress regarding the mechanism that control its basal transcription and regulation has been made. It has been identified several important elements that responsible for the transcription of the TATA-less FSHR gene such as: E box element (CACG(A)TG, –124/–119), an inverted GATA (TATC, –88/–85), E2F (TTTCGCG, –45/–39), and regulator element-3 (–197/–171). The functional studies shown that mutations through these regulatory elements significantly decrease the promoter function with greatest impact detected when mutation was done in E-box element. The site-specific CpG methylation within the core promoter seems play an important role in the regulation of rat and mouse FSHR gene expression. (Med J Indones 2003; 12: 187-93)